PIM kinases: From survival factors to regulators of cell motility - Santio Niina; Koskinen Päivi (Elsevier Ltd, 2025)
PIM kinases are oncogenic serine/threonine kinases, the expression and activities of which are tightly regulated in normal tissues, but upregulated in many types of human malignancies, including both hematological and solid cancers. Since high PIM expression levels have been connected to cancer progression and poor patient survival, PIM kinases have become attractive targets for drug development. Many downstream targets have also been identified, through which PIM kinases promote cell survival, proliferation and metabolism. More recently, PIM kinases have been implicated in regulation of cell motility, which also plays an important role in tumor growth and cancer progression. This review summarizes effects of PIM kinases and their substrates especially on cancer cell migration, invasion and metastatic growth, based on data from cell-based assays, animal experiments and patients.